Characterization of EHop-016, Novel Small Molecule Inhibitor of Rac GTPase - Montalvo-Ortiz, Brenda L. (American Society for Biochemistry and Molecular Biology, 2012)
The Rho GTPase Rac regulates actin cytoskeleton reorganization to form cell surface extensions (lamellipodia) required for cell migration/invasion during cancer metastasis. Rac hyperactivation and overexpression are associated with aggressive cancers; thus, interference of the interaction of Rac with its direct upstream activators, guanine nucleotide exchange factors (GEFs), is a viable strategy for inhibiting Rac activity. We synthesized EHop-016, a novel inhibitor of Rac activity, based on the structure of the established Rac/Rac GEF inhibitor NSC23766. Herein, we demonstrate that EHop-016 inhibits Rac activity in the MDA-MB-435 metastatic cancer cells that overexpress Rac and exhibits high endogenous Rac activity. The IC(50) of 1.1 μm for Rac inhibition by EHop-016 is ∼100-fold lower than for NSC23766. EHop-016 is specific for Rac1 and Rac3 at concentrations of ≤5 μm. At higher concentrations, EHop-016 inhibits the close homolog Cdc42. In MDA-MB-435 cells that demonstrate high active levels of the Rac GEF Vav2, EHop-016 inhibits the association of Vav2 with a nucleotide-free Rac1(G15A), which has a high affinity for activated GEFs. EHop-016 also inhibits the Rac activity of MDA-MB-231 metastatic breast cancer cells and reduces Rac-directed lamellipodia formation in both cell lines. EHop-016 decreases Rac downstream effects of PAK1 (p21-activated kinase 1) activity and directed migration of metastatic cancer cells. Moreover, at effective concentrations (<5 μm), EHop-016 does not affect the viability of transformed mammary epithelial cells (MCF-10A) and reduces viability of MDA-MB-435 cells by only 20%. Therefore, EHop-016 holds promise as a targeted therapeutic agent for the treatment of metastatic cancers with high Rac activity.